Footwear Usage in Children with Flatfoot Disorder in Sukajadi Sub-district, Bandung - Wulan Mayasari; Elta Sholihah Putri; Fathurachman Fathurachman (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Flatfoot is a musculoskeletal disorder of the foot where the medial longitudinal arch becomes flatter, resulting in a more foot surface touching the ground compared to the normal foot. One of the risk factors for flatfoot is the rather early footwear usage with a considerably long period of usage with the enclosed footwear type. This may cause weakening of supporting tissues of the foot. This study aimed to describe the use of footwear in children with flatfoot.Methods: This study used a descriptive categorical method, conducted from March to June 2017 among students from five elementary schools in Sukajadi sub-district, Bandung. Primary data were obtained by using questionnaires and descriptively presented.Results: Prevalence of flatfoot among included students (n73) of the elementary school with age range of 6–10 years was 54.8%. All students had their first years of wearing footwear in the age range 0-5 years. The majority (52.5%) of footwear usage duration in flatfoot disorder was ≥8 hours/day, and the footwear type of flatfoot disorder was dominated (65%) by sandals/slippers.Conclusions: There is a high number of flatfoot in elementary school, and this needs special attention, especially on how to use the footwear.